Dark ideas : how neo-Nazi and violent jihadi ideologues shaped modern terrorism - Morris, Travis, 1973- (Lexington Books, 2017)
Dark Ideas provides readers with a different method of understanding how ideas can transform violent extremism. Over recent decades, violent jihadi and neo-Nazi ideologues have continued to promote new strategic and tactical innovations that shaped the evolution of terrorism. Many of these "dark" innovations have now become accepted practices by groups and individuals, yet they are rarely examined